Divergent controls on nitrogen and phosphorus export regimes across Chinese catchments - Xu Yang; Haojie Han; Xing Yan; Yuting Xie; Yanyu Ren; Yuhang Zhang; Daming Yang; Dongli She; Xuan Huang; Yongqiu Xia (Water Research, 2026)

The role and mechanism of TNFRSF21 in promoting necroptosis of vascular endothelial cells and inducing vascular leakage in sepsis - Juntao Wang; Bindan Zhang; Yujia Wu; Weichao Li; Yuxi Zhang; Daiqin Bao; Haoyu Pei; Caifeng Shi; Han She; Xiaoyan Wang; Qingxiang Mao; Cong Yu (Journal of Molecular Medicine, 2026)

Genomic and biosynthetic landscape of high-temperature Daqu microbiome - Mingyue Cheng; Xing Qin; Ying Han; Fanggen Tan; Menglin She; Xue Zhu; Lin Yuan; Mengjing Teng; Xiyang Ou; Sha Luo; Ping Xiang; Liangqiang Chen; et al. (Bioresource Technology, 2026)

Tb3+/Eu3+ ratiometric fluorescent probes for food safety monitoring: from mechanistic design to portable detection platforms - Jing Cao; Mengmeng Chen; Miao Wang; Ying Han; Shiyao Fu; Yongxin She; Xin Yang; Jing Wang (Trends in Food Science & Technology, 2026)

An all-in-one endoluminal acoustofluidic system enables spatiotemporal transmucosal drug delivery and barrier repair for inflammatory bowel disease - Yichen Liu; Xiaoming Zheng; Yang Qin; Jing Han; Zhiwei Cong; Shu Fan; Yan Li; Ruochen Wang; Xiaolong Guo; Qichao Huang; Xunan Jing; Yibo Liu; et al. (Chemical Engineering Journal, 2026)

Integrating multiple water quality indices with explainable machine learning models to assess drinking water suitability of river waters in an alluvial plain - Yungang Wu; Yuankang Zhong; Haidong Li; Zhi Su; Qian Han; Lei Chen; Meizhu Zhou; Yunhui Zhang; Chengyue Lai; Jia She (Journal of Water Process Engineering, 2026)

Particle Type- and Morphology-Associated Neurotoxicity of Microplastics and Nanoplastics via Divergent PPARγ Modulation in Zebrafish - Chenchen Han; Lixia Peng; Xinlei Guo; Yaqi Yu; Mingming Niu; Willie J.G.M. Peijnenburg; Zhiqiang Li; Xilin She; Chuanhong Wu; Lianzhen Li (Journal of Hazardous Materials, 2026)

Rhamnolipid@Ag bio-nanofluids for enhanced oil recovery: Multiscale experimental and molecular mechanism elucidation - Yuxiao Han; Shuyuan Deng; Jian Fu; Bo Wang; Jie Gao; Ming Nie; Qijun Wu; Yuehui She; Fan Zhang (Journal of Cleaner Production, 2026)

Assessing additive interactions of heat wave, fine particulate matter, and ozone on cardiovascular mortality in a typical cold region of China: A time-stratified case-crossover study - Jinghao Wan; Mingzhao She; Hanhan Wang; Lixin Zheng; Xinyue Yu; Yuqian Song; Zhongran Wang; Min Li; Xu Han; Haibo Zhou; Zhifeng Xing; Xiao Bai; et al. (International Journal of Hygiene and Environmental Health, 2026)

Palaeochannels as hidden pathways of water flow in agricultural alluvial landscapes: A review of concepts and suggested future directions for modelling - Han She Lim; Alexander W. Cheesman; Paul N. Nelson; Rohan Eccles; Felix Egger; Marcus Bulstrode; Tony Weber (Journal of Hydrology, 2026)

Performance and multiscale mechanistic investigation of microbially derived green carbon quantum dot–rhamnolipid bionanocomposites for enhanced oil recovery in low-permeability reservoirs - Yuxiao Han; Fan Zhang; Jie Gao; Xiaorui Chang; Landuo Li; Chengjie Yan; Miaomiao Hu; Yujiao Zhao; Yuehui She (Chemical Engineering Journal, 2026)

Lower levels of oxygen content and carbon-to-nitrogen ratio in sludge drying off-gas balances simultaneous anammox and denitrification in a membrane biofilm reactor for synergistic bio-decontamination of trimethylamine and nitric oxide - Yuan Zeng; Xiu-Qin Tan; Lu-Lu Sun; Jia-Hua Wu; Han-Biao Yang; Zhen-Shan Huang; She-Jun Chen; Zai-Shan Wei (Bioresource Technology, 2026)

Development of a pomelo pectin–based microencapsulation system for Akkermansia muciniphila - Chang-Han Wang; Wen-Yu Liu; She-Ching Wu (Food Chemistry, 2026)

Enhanced Therapeutic Effects of Extracellular Vesicles Targeting MiR-137 Contribute to Functional Recovery by Attenuating Neuronal Injury After Ischemic Stroke - Hui-Xin Zhang; Li-Qing Tao; Yi-Hang Chen; Tian-Yi Jiang; Zhi-Yuan Ye; Wen She; Chang-Ying Chen; Ya-Li Han; Cui Qi; Chong Shen; Jun Gao (Neuroscience Bulletin, 2026)

Transcriptomic analysis identifies VvMYB90 and VvNAC92 as key regulators mediating anthocyanin biosynthesis and fruit color differentiation in three grape cultivars - Han Lin; Kaili Mao; Shilong Chai; Jiangmin Lan; Hongbo Xiao; Zhixiong Guo; Tengfei Pan; Wenqin She (Plant Science, 2026)

Patterns of phylogenetic structure across plant life-forms in a large temperate forest and their possible drivers - Yanbo Yang; Danqi She; Yuhong Zhang; Jinghua Yu; Lihua Wang; Huimei Wang; Shijie Han; Wenjie Wang (Biodiversity and Conservation, 2026)

TRAF7 protects against acute lung injury by promoting K6-linked ubiquitination of AKT - Jia Wang; Meng-Liu Zeng; Ya-Zhou Sun; Xu-Tao Zhang; Xin-Yan Li; Wei-Yi Qu; Wei Li; Jia-Yi Liu; Xu Cheng; Jun Zhang; Han Tian; Hui Liu; et al. (Science Bulletin, 2026)

Few-shot natural frequency prediction of Camellia oleifera for vibration harvesting enabled by synthetic data generation - Feng Liu; Dongying Mo; Han Fu; Shaozheng Yu; Xuan Chu; Nan She; Xing Xu; Weizu Wang; Jieli Duan (Computers and Electronics in Agriculture, 2026)

Nonlinear dynamics of rotating graphene-reinforced composite blades under 1:2 internal resonance in fluid-submerged environments - Yi-Han Cheng; Gui-Lin She (Ocean Engineering, 2025)

Relating small waterbody denitrification with ecosystem respiration in an intensive anthropogenic region - Xuemei Zhao; Yi Zhu; Xu Yang; Li Zhang; Xuan Huang; Chunwang Li; Kebing Chen; Han Lin; Dongli She; Yongqiu Xia (Journal of Hydrology, 2025)

Green synthesis and functionalization of rice husk-derived SiO₂ nanoparticles for scale inhibition: A multiscale study combining experiments, molecular dynamics simulations, and quantum chemical calculations - Yuxiao Han; Shuyuan Deng; Jian Fu; Bo Wang; Jie Gao; Ming Nie; Qijun Wu; Yuehui She; Fan Zhang (Chemical Engineering Journal, 2025)

Characterization of a novel biosurfactant from Alcanivorax dieselolei and its mechanism for enhanced oil recovery in low-permeability reservoirs - Shuyuan Deng; Bo Wang; Ruixue Qu; Yuxiao Han; Cenqian Zhang; Chenyue Wang; Jian Fu; Shanshan Sun; Hao Dong; Gongze Cao; Qing You; Yuehui She; et al. (Chemical Engineering Journal, 2025)

Crystal-scale heterogeneity of Sn isotopes in Cassiterite: implications for reconstructing ore-forming processes in magmatic-hydrothermal systems - Liang Han; Guo-Guang Wang; Pei Ni; Jun-Yi Pan; Jia-Xin She; Wei Tan; Weiqiang Li (Geochimica et Cosmochimica Acta, 2025)

Z-scheme heterojunction engineered covalent organic polymer for thermodynamically optimized CO2 photoreduction - Jiaxin Rong; Xuejing Li; Qiang Xu; Jingwei Han; Jing Zhang; Ke Ren; Ping She; Jun-Sheng Qin; Heng Rao (Chemical Engineering Journal, 2025)

A laser with instability reaching 4 × 10 - 17 based on a 10-cm-long silicon cavity at sub-5-K temperatures - Zhi-Ang Chen; Hao-Ran Zeng; Wen-Wei Wang; Han Zhang; Run-Qi Lei; Jian-Zhang Li; Cai-Yin Pang; She-Song Huang; Xibo Zhang (Science Bulletin, 2025)

Pore-size control mechanism of support membranes on interfacial polymerization process: Achieving charge enhancement and optimizing NFMs performance - Ziping Song; Hongjin Yan; Jiahui Li; Jingguo She; Sihua Liu; Zhongrui Chen; Le Shi; Haoyu Zhan; Qijia Han; Xiaolong Lu; Chunrui Wu (Journal of Environmental Chemical Engineering, 2025)

Integrating HS-SPME-GCMS with chemometrics for identifying adulterated flaxseed oils and tracing origins of additives - Yan-Jin Wen; Long-He Wang; Meng Zhai; Hui Ma; Hua-Peng Cui; Lu Han; Guo-Bi Chai; Yi Lv; Qing-Xia Zheng; Yong-Jie Yu; Yuan-bin She (Food Control, 2025)

Synergistic microaerobic bio-decontamination of dimethyl sulfide and elemental mercury in the low-O2 content flue gas by a sulfur-oxidizing membrane biofilm reactor - Han-Biao Yang; Lu-Lu Sun; Xiu-Qin Tan; Yuan Zeng; Yu-Qi Huang; Zhen-Shan Huang; She-Jun Chen; Zai-Shan Wei (Chemical Engineering Journal, 2025)

Unlocking the synergistic effects in biomass-plastic Co-pyrolysis using a hybrid machine learning approach with blended rule descriptors - Peng Jiang; Wenjie She; Hao Zhang; Lin Li; Han Lin; Tuo Ji; Liwen Mu; Xiaohua Lu; Jiahua Zhu (Biomass and Bioenergy, 2025)

Plasma-Derived Exosomal tRF-Phe-GAA-001 and tRF-Gly-GCC-037 as Novel Diagnostic Biomarkers for Cervical Cancer - Zheng Li; Hongyan Wang; Ruijun Yang; Xiangchun Jin; Qing Han; Zhaoyuan She; Peng Ge (Indian Journal of Clinical Biochemistry, 2025)

Oral HMPB/Mn3O4 nanozymes for the treatment of ulcerative colitis via cellular redox balance regulation, gut microbiota modulation, and ferroptosis inhibition - Han Wang; Yexin Liu; Rui Huang; Weirui Chen; Luxuan Chen; Huacai Shi; Si Lei; Qi He; Ri Chen; Lihua Zhou; Wenxia Wang; Yanling She (Chemical Engineering Journal, 2025)

Creating easily accessible adsorption sites in natural wood-derived hierarchical porous carbon via a controlled delignification strategy for organic pollutant removal - Minjiao Chen; Meihua Li; Peng Jiang; Wenjie She; Han Lin; Jiahua Zhu (Biomass and Bioenergy, 2025)

Electrospinning preparation of NaA zeolite composite polyacrylonitrile membranes (NaA@PANMs) and studying on adsorption performance for Sr2+ - Yu Liu; Min Yi; Tao Han; Xinlong Li; Linqiao Qin; Yu She; Erna Wei; Kaituo Wang (Environmental Research, 2025)

A scaling approach for binary and grey computed tomography imaging of soil: A study in a coastal reclamation area - Xiaoqin Sun; Ana M. Tarquis; Dongli She; Xiao Han; Hongde Wang; Shengqiang Tang; Lei Gao; Pei Xin (CATENA, 2025)

Calcium-O-Sr-Nd isotope evidence for the origin of REE-bearing carbonatite from metasomatized lithospheric mantle without recycled carbonate - Xing-Hui Li; Ming-Cai Xie; Kui-Feng Yang; Kan Li; Chun-Ming Han; Hai-Dong She; Gai-Zhong Liang; Xiao-Chun Li; Hong-Rui Fan (Contributions to Mineralogy and Petrology, 2025)

Trace solvents-assisted mechanochemistry of waste poly(ethylene terephthalate) into MIL-53Al for efficient hydroelectricity generation - Yan She; Weikang Han; Huajian Liu; Guixin Hu; Huiyue Wang; Xueying Wen; Lijie Liu; Lingling Feng; Xinyao Zhang; Jiang Gong (Chemical Engineering Journal, 2025)

Glutaminolysis and α-ketoglutarate-stimulated KCa3.1 expression contribute to β-adrenoceptor activation-induced myocardial fibrosis in mice - Ru-Yue Bai; Lin-Hong Wu; Yan Wang; Chen Guo; Gang She; Zheng-Da Pang; Jing-Jing Li; Xin-Yi Zhao; Meng-Zhuan Han; Xia-Xia Hai; Yi-Yi Yang; Yi Zhang; et al. (Science China Life Sciences, 2025)

Comprehensive analysis of spatiotemporal heterogeneity reveals the effects of physicochemical and biological factors on temperature rise during the Moutai-flavor Baijiu stacking fermentation process - Yuanbu Li; Xing Qin; Xianglian Zeng; Menglin She; Liangqiang Chen; Jianjun Lu; Ying Han; Fan Yang; Huabin Tu; Hai Du; Yan Xu (Chemical Engineering Journal, 2025)

In situ construction of cobalt phthalocyanine covalent organic polymer on mesoporous graphitic carbon nitride for boosting photocatalytic CO2 reduction - Jiaxin Rong; Qiang Xu; Jingwei Han; Ke Ren; Jing Zhang; Xue Zhao; Ping She; Jun-Sheng Qin; Heng Rao (Chemical Engineering Journal, 2025)

Nicotinamide riboside restores nicotinamide adenine dinucleotide levels and alleviates brain injury by inhibiting oxidative stress and neuroinflammation in a mouse model of intracerebral hemorrhage - Jing She; Hua Zhang; Hui Xu; Yan-Yan Li; Jun-Chao Wu; Rong Han; Fang Lin; Yan Wang; Rui Sheng; Jin-hua Gu; Zheng-Hong Qin (Molecular Neurobiology, 2025)
Hemorrhagic stroke is a global health problem owing to its high morbidity and mortality rates. Nicotinamide riboside is an important precursor of nicotinamide adenine dinucleotide characterized by a high bioavailability, safety profile, and robust effects on many cellular signaling processes. This study aimed to investigate the protective effects of nicotinamide riboside against collagenase-induced hemorrhagic stroke and its underlying mechanisms of action. An intracerebral hemorrhage model was constructed by stereotactically injecting collagenase into the right striatum of adult male Institute for Cancer Research mice. After 30 minutes, nicotinamide riboside was administered via the tail vein. The mice were sacrificed at different time points for assessments. Nicotinamide riboside reduced collagenase-induced hemorrhagic area, significantly reduced cerebral water content and histopathological damage, promoted neurological function recovery, and suppressed reactive oxygen species production and neuroinflammation. Nicotinamide riboside exerts neuroprotective effects against collagenase-induced intracerebral hemorrhage by inhibiting neuroinflammation and oxidative stress.

Associations between magnesium depletion score and depression among individuals aged 20 to 60 years - Zongao Cai; Jiachen She; Xiaozhu Liu; Ruihui Li; Shuang Guo; Zeyang Han; Jiyang Zhou; Hairong Zhang; Yudi Xu; Ge Zhang; Zhaokai Zhou; Xueli Guo; et al. (Journal of Trace Elements in Medicine and Biology, 2024)

Preparation and optimization of sulfur ferrous inorganic carbon composite filler for autotrophic denitrification nitrogen and phosphorus removal - Changying Pei; Bolin Li; Xiang Li; Jing Wang; Han Zhang; Xiaoguo Chen; Jian She (Journal of Environmental Management, 2024)

Mechanistic insights into tris(2-chloroisopropyl) phosphate biomineralization coupled with lead (II) biostabilization driven by denitrifying bacteria - Zhen-Shan Huang; Xiu-Qin Tan; Han-Biao Yang; Yuan Zeng; She-Jun Chen; Zai-Shan Wei; Yu-Qi Huang (Science of The Total Environment, 2024)

The value of pocket parks in preserving urban butterfly diversity - Shujing Zhang; Dan Han; Junying She; Qing Shen; Cheng Wang (Urban Forestry & Urban Greening, 2024)

Tree richness increased biomass carbon sequestration and ecosystem stability of temperate forests in China: Interacted factors and implications - Kai Wang; Danqi She; Xiting Zhang; Yuanyuan Wang; Hui Wen; Jinghua Yu; Qinggui Wang; Shijie Han; Wenjie Wang (Journal of Environmental Management, 2024)

Petrogenesis of the eudialyte-bearing syenite and indication for Nb-Zr-REE mineralization in Bashisuogong, Northwest China - Mingcai Xie; Chunming Han; Hongrui Fan; Kuifeng Yang; Haidong She; Ziyuan Li (Lithos, 2024)

High-frequency monitoring during rainstorm events reveals nitrogen sources and transport in a rural catchment - Xuan Huang; Yi Zhu; Han Lin; Dongli She; Ping Li; Man Lang; Yongqiu Xia (Journal of Environmental Management, 2024)

Aridity drives the variability of desert soil microbiomes across north-western China - Lei Dong; Mei-Xiang Li; Shuai Li; Ling-Xiang Yue; Mukhtiar Ali; Jia-Rui Han; Wen-Hui Lian; Chao-Jian Hu; Zhi-Liang Lin; Guo-Yuan Shi; Pan-Deng Wang; Shao-Ming Gao; et al. (Science of The Total Environment, 2024)

Corrigendum to “Cytoprotective effect of deferiprone against aluminum chloride-induced oxidative stress and apoptosis in lymphocytes” [Toxicol. Lett. 285 (2018) 132–138] - Cuicui Zhuang; Yue She; Haiyang Zhang; Miao Song; Yanfei Han; Yanfei Li; Yanzhu Zhu (Toxicology Letters, 2023)

A novel 3D-fluorescence sensing strategy based on HN-chitosan polymer probe for rapid identification and quantification of potential adulteration in saffron - Wanjun Long; Gaoqiong Deng; Yanmei Zhu; Qingyang Han; Hengye Chen; Yuanbin She; Haiyan Fu (Food Chemistry, 2023)

Evaluation of the relationship of wastewater treatment and biodiesel production by microalgae cultivated in the photobioreactor - Qingyun Zhao; Fei Han; Zhanping You; Yuhong Huang; Xiaohui She (Fuel, 2023)

Using UHPLC-HRMS-based comprehensive strategy to efficiently and accurately screen and identify illegal additives in health-care foods - Meng-Han Ma; Jia-Ni Zhang; Xing-Ling Ma; Xing-Cai Wang; Feng-Lian Ma; Jia-Nan Liu; Yi Lv; Yong-Jie Yu; Yuanbin She (Food Research International, 2023)

Competitive fluorescent immunosensor based on catalytic hairpin self-assembly for multiresidue detection of organophosphate pesticides in agricultural products - Yuanshang Wang; A.M. Abd El-Aty; Shanshan Wang; Xueyan Cui; Jing Zhao; Xingmei Lei; Lingyuan Xu; Yongxin She; Fen Jin; Jong-Bang Eun; Jae-Han Shim; Jing Wang; et al. (Food Chemistry, 2023)

In-drain denitrifying woodchip bioreactors for reducing nitrogen runoff from sugarcane - Alexander W. Cheesman; Shannon Todd; Liz Owen; Dennis AhKee; Han She Lim; Maureen Masson; Paul N. Nelson (Ecological Engineering, 2023)

Field trial assessing the antimicrobial decontamination efficacy of gaseous ozone in a public bus setting - Erica Sena Neves; Cheng Teng Ng; Han Bin Pek; Vanessa Shi Li Goh; Roslinda Mohamed; Sheereen Osman; Yi Kai Ng; Sharain Abdul Kadir; Mohammad Nazeem; Alan She; Glenndle Sim; Joel Aik; et al. (Science of The Total Environment, 2023)

A study of flavor variations during the flaxseed roasting procedure by developed real-time SPME GC–MS coupled with chemometrics - Xing-Ling Ma; Xing-Cai Wang; Jia-Ni Zhang; Jia-Nan Liu; Meng-Han Ma; Feng-Lian Ma; Yi Lv; Yong-Jie Yu; Yuanbin She (Food Chemistry, 2023)

A comparison of feature extraction capabilities of advanced UHPLC-HRMS data analysis tools in plant metabolomics - Xing-Cai Wang; Xing-Ling Ma; Jia-Nan Liu; Yang Zhang; Jia-Ni Zhang; Meng-Han Ma; Feng-Lian Ma; Yong-Jie Yu; Yuanbin She (Analytica Chimica Acta, 2023)

Variations in the CT-measured pore structure and hydraulic characteristics of coastal saline soils with different reclamation periods - Han Xiao; She Dongli; Sun Xiaoqin; Fei Yuanhang; Gao Lei (Journal of Soils and Sediments, 2023)

Drought trigger thresholds for different levels of vegetation loss in China and their dynamics - Wenwen Guo; Shengzhi Huang; Qiang Huang; Guoyong Leng; Zhenxia Mu; Zhiming Han; Xiaoting Wei; Dunxian She; Hanye Wang; Zhixia Wang; Jian Peng (Agricultural and Forest Meteorology, 2023)

Multidimensional analysis of the essential elements in pregnant women's whole blood and characterization of maternal status by elemental pattern - Min Zhan; Wenbin Chen; Zhichao Wang; Xuhui She; Qiaoxuan Zhang; Heng Dong; Jun Yan; Zhuoyang Li; Liqiao Han; Haibiao Lin; Xianzhang Huang; Beibei Zhao (Journal of Trace Elements in Medicine and Biology, 2023)

Modified effects of air pollutants on the relationship between temperature variability and hand, foot, and mouth disease in Zibo City, China - Chunyu Li; Yuchen Zhu; Kaili She; Yan Jia; Tingxuan Liu; Chuang Han; Qidi Fang; Chuanlong Cheng; Luyi Han; Ying Liu; Ying Zhang; Xiujun Li (Environmental Science and Pollution Research, 2022)

Eye-Opening Alters the Interaction Between the Salience Network and the Default-Mode Network - Junrong Han; Xuehai Wu; Hang Wu; Dong Wang; Xuan She; Musi Xie; Fang Zhang; Delong Zhang; Xilin Zhang; Pengmin Qin (Neuroscience Bulletin, 2020)

In vitro dual-target activities and in vivo antidiabetic effect of 3-hydroxy-N-(p-hydroxy-phenethyl) phthalimide in high-fat diet and streptozotocin-induced diabetic golden hamsters - Bin Xiao; Yunfeng Xiao; Haining Ning; Xiaoyan Han; Wenyan Li; Yuheng Ma; Na Zhao; Guanhua Du; Yu Dong; Jee H. Jung; Zhanfei She (Medicinal Chemistry Research, 2020)

Characteristics of single atmospheric particles in a heavily polluted urban area of China: size distributions and mixing states - Li Li; Qiyuan Wang; Xu Zhang; Yuanyuan She; Jiamao Zhou; Yang Chen; Ping Wang; Suixin Liu; Ting Zhang; Wenting Dai; Yongming Han; Junji Cao (Environmental Science and Pollution Research, 2019)

Sumoylation of SUVR2 contributes to its role in transcriptional gene silencing - Yu-Xi Luo; Yong-Feng Han; Qiu-Yuan Zhao; Jin-Lu Du; Kun Dou; Lin Li; She Chen; Xin-Jian He (Science China Life Sciences, 2018)

Genetic technologies for extremely thermophilic microorganisms of Sulfolobus, the only genetically tractable genus of crenarchaea - Nan Peng; Wenyuan Han; Yingjun Li; Yunxiang Liang; Qunxin She (Science China Life Sciences, 2017)

The heterogeneity of islet autoantibodies and the progression of islet failure in type 1 diabetic patients - Jin Liu; Lingling Bian; Li Ji; Yang Chen; Heng Chen; Yong Gu; Bingqin Ma; Wei Gu; Xinyu Xu; Yun Shi; Jian Wang; Dalong Zhu; et al. (Science China Life Sciences, 2016)

Chryseobacterium chengduensis sp. nov. isolated from the air of captive giant panda enclosures in Chengdu, China - Cai-fang Wen; Li-xin Xi; Shan Zhao; Zhong-xiang Hao; Lu Luo; Hong Liao; Zhen-rong Chen; Rong She; Guo-quan Han; San-jie Cao; Rui Wu; Qi-gui Yan; et al. (Journal of Zhejiang University-SCIENCE B, 2016)

Lysobacter chengduensis sp. nov. Isolated from the Air of Captive Ailuropoda melanoleuca Enclosures in Chengdu, China - Caifang Wen; Lixin Xi; Rong She; Shan Zhao; Zhongxiang Hao; Lu Luo; Hong Liao; Zhenrong Chen; Guoquan Han; Sanjie Cao; Rui Wu; Qigui Yan; et al. (Current Microbiology, 2016)

Isolation and characterization of a crude oil degrading bacteria from formation water: comparative genomic analysis of environmental Ochrobactrum intermedium isolate versus clinical strains - Lu-jun Chai; Xia-wei Jiang; Fan Zhang; Bei-wen Zheng; Fu-chang Shu; Zheng-liang Wang; Qing-feng Cui; Han-ping Dong; Zhong-zhi Zhang; Du-jie Hou; Yue-hui She (Journal of Zhejiang University-SCIENCE B, 2015)

Direct cloning, expression of a thermostable xylanase gene from the metagenomic DNA of cow dung compost and enzymatic production of xylooligosaccharides from corncob - Ming-zhe Sun; Hong-chen Zheng; Ling-cai Meng; Jun-she Sun; Hui Song; Yun-juan Bao; Hai-sheng Pei; Zheng Yan; Xiu-qing Zhang; Jing-sheng Zhang; Yi-han Liu; Fu-ping Lu (Biotechnology Letters, 2015)

Shipborne heading determination and error compensation based on a dynamic baseline - Peida Hu; Zhongyu Gao; Yajun She; Long Cai; Fengtian Han (GPS Solutions, 2015)

Aluminum Trichloride Disorders Bile Acid Secretion and Induces Hepatocyte Apoptosis in Rats - Yue She; Hansong Zhao; Yanzhu Zhu; Yanfei Han; Shiliang Xia; Chongsheng Bai; Jihong Zhang; Yanfei Li (Cell Biochemistry and Biophysics, 2015)

Separation method for multi-source blended seismic data - Han-Chuang Wang; Sheng-Chang Chen; Bo Zhang; De-Ping She (Applied Geophysics, 2013)

Modifiers and Amplifiers of High and low Flows on the Ping River in Northern Thailand (1921–2009): The Roles of Climatic Events and Anthropogenic Activity - Han She Lim; Kanokporn Boochabun; Alan D. Ziegler (Water Resources Management, 2012)

Vascular endothelial growth factor-C promotes the growth and invasion of gallbladder cancer via an autocrine mechanism - Yanling Chen; Lei Jiang; Feifei She; Nanhong Tang; Xiaoqian Wang; Xiujin Li; Shenghua Han; Jinhai Zhu (Molecular and Cellular Biochemistry, 2010)

Hepatitis C virus NS2/3 protease regulates HCV IRES-dependent translation and NS5B RdRp activity - Yinglong She; Tao Han; Linbai Ye; Zhenghui Wu (Archives of Virology, 2009)